سؤال الحداثة في الفكر السياسي العربي المعاصر: محمد سبيلا إنموذجاً (قضايا سياسية, 2022)
Modernity is Considered one of the most Important Complex Issues that Political thought Concerned in General, and Contemporary Arab Political thought in Particular, as many Arab Concepts and Researchers were Interested in the question of Modernity and their Concern and the focus of their research was, and at the forefront of these Arab thinkers Muhammad Sabila, as he took Sabila of Modernity An Intellectual Doctrine through which it Seeks to Modernize Arab thought and Reject lived Reality.